The Insight and Limitation of "Post-Theory": The Poetics Problem of Chinese Cinema Carried by David Bordwell. Issue 2 (3rd March 2020) - Yu, Chen
ABSTRACT: David Bordwell has devoted himself to studying the poetics of cinema in terms of the mode and style of films. Bordwell's study of Chinese film poetics has also become a mirror to reflect on the effectiveness and limitation of the middle-level theory as a form of "post theory". Accordingly, "the gweilo 's middle-level (or piecemeal) theories" proved the fundamental methodology for Bordwell to carry out the analysis of the poetics of Chinese cinema. Paying close attention to the action factor of Hong Kong popular cinema and analysing "aesthetics in action", Bordwell indicated that one had to re-understand the question of "popular cinema's recreational and artistic natures". Bordwell analysed Hou's efforts to carry out cinematic staging in terms of "craft" and "technique". Bordwell labelled Hou's cinematic style "lyric realism" and "mature realism". Through middle-level (or piecemeal) theories, he was liable to indulge in minor details, especially when he attempted to deal with the questions of cinematic theories and cinematic history as a whole. Thus, we need to determine both the strong and weak aspects of his analysis of the poetics of Chinese cinema.